Multidrug Resistant Tuberculosis (MDR-TB): Tinjauan Epidemiologi dan Faktor Risiko Efek Samping Obat Anti Tuberkulosis - Reviono; P. Kusnanto; Vicky Eko; Helena Pakiding; Dyah Nurwidiasih (Majalah Kedokteran Bandung, 2014)
The number of Multi drug resistant tuberculosis (MDR-TB) cases is predicted to be increasing. The management of MDR-TB is more complex than susceptible TB due to the resistance to the first and second lines of anti tuberculosis drugs. Leading to anti tuberculosis drugs tolerance and adverse event issues. This study was a cohort study conducted between January 2011 and June 2013 to describe the type, frequency, and risk factors of adverse events caused by drugs. Sputum samples of patients who were suspected to have MDR TB were collected and examined as sputum smears using Ziehl Nielsen staining and Gene Xpert MTB/RIF segment amplification of rpoB gene region methods to assess resistance towards rifampicin. Samples with positive results were cultured in solid medium (Lowenstein Jensen) and liquid medium (Mycobacteria growth indicator tube test,MGIT). This study was conducted in Moewardi General Hospital. The number of confirmed MDR-TB patients was114 subject consisting of 56 males and 58 females. The most common adverse events were gastrointestinal disturbances including nausea 79.8% and vomiting 78.9%. Minor adverse events also found in 76.3% patients. There was a significant relationship between previous anti tuberculosis medication and renal impairment (p=0.026); between sex and renal impairment (p=0.033); and between sex and hearing impairment (p= 0.039). There was no significant relationship between sex and mental illnesses (p=0.062) as well as between previous anti tuberculosis medication and hearing impairment (p=0.115) and between previous anti tuberculosis medication and hypopotassemia (p=0.968),. In conclusion, the major adverse events in MDR-TB cases are gastrointestinal disturbances